Adaptation of a school-based mental health literacy curriculum: from Canadian to English classrooms. (12th October 2021) - Mansfield, Rosie; Humphrey, Neil; Patalay, Praveetha; Moore, Anna; Stapley, Emily
Abstract: Background: School-based mental health literacy (MHL) interventions are increasingly trialled outside of the country in which they were developed. However, there is a lack of published studies that qualitatively explore their cultural adaptation. This study investigated the reasons for adaptations made and suggested to a Canadian MHL curriculum (The Guide) within the English school context. Method: Semi-structured interviews were conducted with 11 school staff responsible for the planning and/or implementation of The Guide across three schools in the South East of England, as part of the Education for Wellbeing (EfW) feasibility study. Transcripts were analysed using a hybrid, deductive-inductive thematic analysis. Results: Adaptations made and suggested included dropping and emphasising content, and adapting language, examples and references. Most adaptations were proactive and related to The Guide's implementation methods, including developing more interactive and student-led approaches. Staff Capacity and Expertise, Timetabling, and Accessibility of Resources were identified as logistical reasons for adaptations. Philosophical reasons included Consistency of Messages, Student Characteristics, Reducing Stigma and Empowering Students, National and Local Context, and Appropriate Pedagogic Practices . Conclusion: Overall, recommendations were for immediately implementable lesson plans informed by teachers' knowledge about best pedagogic practices in England. Adequate training, attended by both senior leadership and those implementing, was also emphasised. While ensuring that the core components are clear, MHL interventions should be developed with a necessary level of flexibility to accommodate contextual characteristics. Future research should ensure that adaptations are captured through process and implementation evaluations conducted alongside efficacy trials.